An innovative method to obtain porous porcine aorta scaffolds for tissue engineering. Issue 12 (1st August 2019) - Liu, Xiaohong; Cai, Yang; Xia, Cuiping; Wu, Hao; Li, Qin; Xu, Zhiyun; Lu, Fanglin
Abstract: Decellularized porcine aorta (PA) is a promising biomaterial for vascular substitutes. However, decellularized PAs suffer from mechanical weakness and have less pores, which limit cellular ingrowth into the grafts and hinder the remodeling. In this study, PAs were decellularized by vacuum‐freeze‐thawing cycles and 0.3% of sodium dodecyl sulfate (SDS) buffer (VLS). Results showed that the application of vacuum‐freeze‐thawing significantly improved the decellularization efficiency of SDS while effectively preserved the mechanical function of PA tissues, decreased residual SDS, and minimized cytotoxicity. Furthermore, scanning electron microscopy (SEM) examination demonstrated that VLS generated interconnected pores with uniform distribution. In vivo subcutaneous implantation assay further demonstrated that VLS implants had less calcification and adverse inflammatory response. Moreover, VLS treatment markedly enhanced ingrowth of myofibroblasts and endothelial cells, and thereby promoted synthesis of extracellular matrix and vascularization. These results suggest that the application of vacuum‐freeze‐thawing into the decellularization process may produce a promising vascular graft candidate for tissue engineering application.